SARS-CoV-2 accessory proteins involvement in inflammatory and profibrotic processes through IL11 signaling - López-Ayllón, Blanca D.; de Lucas-Rius, Ana; Mendoza-García, Laura; García-García, Tránsito; Fernández-Rodríguez, Raúl; Suárez-Cárdenas, José M.; Santos, Fátima Milhano; Corrales, Fernando; Redondo, Natalia; Pedrucci, Federica; Zaldívar-López, Sara; Jiménez-Marín, Ángeles; et al. (Frontiers in Immunology, 2023)
SARS-CoV-2, the cause of the COVID-19 pandemic, possesses eleven accessory proteins encoded in its genome. Their roles during infection are still not completely understood.In this study, transcriptomics analysis revealed that both WNT5A and IL11 were significantly up-regulated in A549 cells expressing individual accessory proteins ORF6, ORF8, ORF9b or ORF9c from SARS-CoV-2 (Wuhan-Hu-1 isolate). IL11 is a member of the IL6 family of cytokines. IL11 signaling-related genes were also differentially expressed. Bioinformatics analysis disclosed that both WNT5A and IL11 were involved in pulmonary fibrosis idiopathic disease and functional assays confirmed their association with profibrotic cell responses. Subsequently, data comparison with lung cell lines infected with SARS-CoV-2 or lung biopsies from patients with COVID-19, evidenced altered profibrotic gene expression that matched those obtained in this study. Our results show ORF6, ORF8, ORF9b and ORF9c involvement in inflammatory and profibrotic responses. Thus, these accessory proteins could be targeted by new therapies against COVID-19 disease.